Thermoelectrics : fundamentals, materials selection, properties, and performance /: fundamentals, materials selection, properties, and performance. ([2019]) - Ravin, N. M; Jariwala, Bhakti; Bañobre, Asahel; Maske, Aniket
No abstract available